Siblinghood and social relations in Georgian England : share and share alike - Harris, Amy (Professor of history) (Manchester University Press, 2016)
This book examines the impact sisters and brothers had on eighteenth-century English families and society. Using evidence from letters, diaries, probate disputes, court transcripts, prescriptive literature and portraiture, it argues that although parents' wills often recommended their children 'share and share alike', siblings had to constantly negotiate between prescribed equality and practiced inequalities. Siblinghood and social relations in Georgian England, which will be the first monograph-length analysis of early modern siblings in England, is primed to be at the forefront of sibling stu.